Molecular characterization of localized pleural mesothelioma - Hung, Yin P. (Mod Pathol, 2019)
Localized pleural mesothelioma is a rare solitary circumscribed pleural tumor that is microscopically similar to diffuse malignant pleural mesothelioma. However, the molecular characteristics and nosologic relationship with its diffuse counterpart remain unknown. In a consecutive cohort of 1110 patients with pleural mesotheliomas diagnosed in 2005–2018, we identified six (0.5%) patients diagnosed with localized pleural mesotheliomas. We gathered clinical history, evaluated the histopathology, and in select cases performed karyotypic analysis and targeted next-generation sequencing. The cohort included three women and three men (median age 63; range 28–76), often presenting incidentally during radiologic evaluation for unrelated conditions. Neoadjuvant chemotherapy was administered in two patients. All tumors (median size 5.0 cm; range 2.7–13.5 cm) demonstrated gross circumscription (with microscopic invasion into lung, soft tissue, and/or rib in four cases), mesothelioma histology (four biphasic and two epithelioid types), and mesothelial immunophenotype. Of four patients with at least 6-month follow-up, three were alive (up to 8.9 years). Genomic characterization identified several subgroups: (1) BAP1 mutations with deletions of CDKN2A and NF2 in two tumors; (2) TRAF7 mutations in two tumors, including one harboring trisomies of chromosomes 3, 5, 7, and X; and (3) genomic near-haploidization, characterized by extensive loss of heterozygosity sparing chromosomes 5 and 7. Localized pleural mesotheliomas appear genetically heterogeneous and include BAP1-mutated, TRAF7-mutated, and near-haploid subgroups. While the BAP1-mutated subgroup is similar to diffuse malignant pleural mesotheliomas, the TRAF7-mutated subgroup overlaps genetically with adenomatoid tumors and well-differentiated papillary mesotheliomas, in which recurrent TRAF7 mutations have been described. Genomic near-haploidization, identified recently in a subset of diffuse malignant pleural mesotheliomas, suggests a novel mechanism in the pathogenesis of both localized pleural mesothelioma and diffuse malignant pleural mesothelioma. Our findings describe distinctive genetic features of localized pleural mesothelioma, with both similarities to and differences from diffuse malignant pleural mesothelioma.